2017
DOI: 10.1080/02656736.2017.1385860
|View full text |Cite
|
Sign up to set email alerts
|

Activation of hypoxia-inducible factor-1α in rat brain after perinatal anoxia: role of body temperature

Abstract: Transcriptional hypoxia-inducible factor-1α (HIF-1α) plays the fundamental role in adaptive processes in response to hypoxia. Specific HIF-1α target genes are involved in glycolysis, erythropoiesis and angiogenesis to promote survival. In our previous study we have demonstrated that naturally low body temperature of newborn rats protects them against damage due to perinatal hypoxia. Therefore, our experiments aimed at checking the effects of body temperature during simulated perinatal anoxia on subsequent chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 60 publications
1
5
1
Order By: Relevance
“…By contrast, our up‐to‐date studies have shown that neonatal anoxia combined with hyperthermia intensified the postanoxic oxidative stress (Kletkiewicz, Rogalska, et al, ), depleted the cerebral pool of antioxidant enzymes and low molecular weight antioxidants (Kletkiewicz, Nowakowska, et al, ). Consistently, we have also shown that thermal stress conditions (hyperthermic, extremely hyperthermic) decreased the HIF‐1α level in the hippocampus of animals exposed to anoxia (Kletkiewicz, Hyjek, Jaworski, Nowakowska, & Rogalska, ). On the other hand, neuroprotective effects of decreased temperature in newborn rats are multifunctional (Cerio et al, ).…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…By contrast, our up‐to‐date studies have shown that neonatal anoxia combined with hyperthermia intensified the postanoxic oxidative stress (Kletkiewicz, Rogalska, et al, ), depleted the cerebral pool of antioxidant enzymes and low molecular weight antioxidants (Kletkiewicz, Nowakowska, et al, ). Consistently, we have also shown that thermal stress conditions (hyperthermic, extremely hyperthermic) decreased the HIF‐1α level in the hippocampus of animals exposed to anoxia (Kletkiewicz, Hyjek, Jaworski, Nowakowska, & Rogalska, ). On the other hand, neuroprotective effects of decreased temperature in newborn rats are multifunctional (Cerio et al, ).…”
Section: Introductionsupporting
confidence: 75%
“…Anoxia was induced in 2‐day‐old Wistar rats ( n = 57) using the procedure previously adapted and described in earlier papers (Kletkiewicz et al, ; Kletkiewicz, Nowakowska, et al, ; Kletkiewicz, Rogalska, et al, ). Briefly, prior to experiments, thermocouples connected to the recording system (3000‐E52 Iso‐Thermex Interface & Software, USA) were inserted 5 mm into the colon of the rat pups.…”
Section: Methodsmentioning
confidence: 99%
“…HIF-1, which is composed of two subunits, α and β, can participate in glycolysis metabolism and erythropoiesis and is relatively stable during hypoxia ( Semenza, 2014 ). Some studies have shown that HIF-1α in newborn rats significantly increases during hypoxia ( Kletkiewicz et al, 2018 ). Chu et al (2016 ) used CoCl 2 to establish a hypoxia model of breast cancer cells and found that the expression of HIF-1α mRNA was increased in those cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly Hypoxia can impair metabolic pathways in the brain as well and activate immune cells that are usually maintained in a resting state during normoxia. The hypoxia microenvironment in the brain actives hypoxia inducible factor 1 (HIF-1α) which is a key regulator of oxygen homeostasis and triggers adoptive responses under hypoxic conditions (73). HIF-1α down regulates the expression of ACE2 and transmembrane protease serine 2 (TMPRSS2) and so can exert a protective effect by blocking of the cell entry gate of SARS-CoV-2 (74,75).…”
Section: Cns Injury and The Immune Response In Covid-19mentioning
confidence: 99%